Influence of the pressure field distribution in transcranial ultrasonic neurostimulation. Issue 8 (16th July 2013) - Younan, Youliana; Deffieux, Thomas; Larrat, Benoit; Fink, Mathias; Tanter, Mickael; Aubry, Jean‐Francois
Abstract : Purpose: : Low‐intensity focused ultrasound has been shown to stimulate the brain noninvasively and without noticeable tissue damage. Such a noninvasive and localized neurostimulation is expected to have a major impact in neuroscience in the coming years. This emerging field will require many animal experiments to fully understand the link between ultrasound and stimulation. The primary goal of this paper is to investigate transcranial ultrasonic neurostimulation at low frequency (320 kHz) on anesthetized rats for different acoustic pressures and estimate the in situ pressure field distribution and the corresponding motor threshold, if any. The corresponding acoustic pressure distribution inside the brain, which cannot be measured in vivo, is investigated based on numerical simulations of the ultrasound propagation inside the head cavity, reproducing at best the experiments conducted in the first part, both in terms of transducer and head geometry and in terms of acoustic parameters. Methods: : In this study, 37 ultrasonic neurostimulation sessions were achieved in rats ( N = 8) using a 320 kHz transducer. The corresponding beam profile in the entire head was simulated in order to investigate the in situ pressure and intensity level as well as the spatial pressure distribution, thanks to a rat microcomputed tomography scan (CT)‐based 3D finite differences time domain solver. Results: : Ultrasound pulse evoked a motor response in more than 60% of the experimental sessions. In those sessions, the stimulation was always present, repeatable with a pressure threshold under which no motor response occurred. This average acoustic pressure threshold was found to be 0.68 ± 0.1 MPa (corresponding mechanical index, MI = 1.2 and spatial peak, pulse averaged intensity, Isppa = 7.5 W cm −2 ), as calibrated in free water. A slight variation was observed between deep anesthesia stage (0.77 ± 0.04 MPa) and light anesthesia stage (0.61 ± 0.03 MPa), assessed from the pedal reflex. Several kinds of motor responses were observed: movements of the tail, the hind legs, the forelimbs, the eye, and even a single whisker were induced separately. Numerical simulations of an equivalent experiment with identical acoustic parameters showed that the acoustic field was spread over the whole rat brain with the presence of several secondary pressure peaks. Due to reverberations, a 1.8‐fold increase of the spatial peak, temporal peak acoustic pressure (Psptp) (±0.4 standard deviation), a 3.6‐fold increase (±1.8) for the spatial peak, temporal peak acoustic intensity (Isptp), and 2.3 for the spatial peak, pulse averaged acoustic intensity (Isppa), were found compared to simulations of the beam in free water. Applying such corrections due to reverberations on the experimental results would yield a higher estimation for the average acoustic pressure threshold for motor neurostimulation at 320 KHz at 1.2 ± 0.3 MPa (MI = 2.2 ± 0.5 and Isppa = 17.5 ± 7.5 W cm −2 ). Conclusions: : Transcranial ultrasonic stimulation is pressure‐ and anesthesia‐dependent in the rat model. Numerical simulations have shown that the acoustic pattern can be complex inside the rat head and that special care must be taken for small animal studies relating acoustic parameters to neurostimulation effects, especially at a low frequency.